Switchable band-stop to all pass filter using stepped impedance resonator - Bakhit, A.A. (2013)
The exponential growth of the modern wireless communications market creates an unprecedented demand for compact-size, low-cost, high-performance and a reconfigurable filter. Due to this recent development, much attention has been devoted to compact microwave reconfigurable filters. This paper discusses and delves into the design of novel switchable band-stop to all pass filters. This filter is realized by using a stepped impedance resonator, by incorporating the PIN diodes into the topology as switching elements. It results in two modes of operation under two conditions; in the first condition, the filter will produce a band-stop response when the PIN diodes are switched 'ON', and in the second condition, the filter will produce an all pass response when the PIN diodes are switched 'OFF'. Theoretical analysis of the approach is presented in this paper, and its feasibility has been experimentally verified with a micro-strip circuit prototype. The measured result shows that the insertion loss S(1, 2) in band-stop mode of an operation is around 38 dB, while the return loss S(1, 1) is around 27 dB. For the all-pass mode of operation, the insertion loss is totally flat at 0 dB, while the return loss is around 17 dB, making it suitable for wireless communication.